Congenital Mirror Movements Associated With Brain Malformations. (June 2021) - Nissenkorn, Andreea; Yosovich, Keren; Leibovitz, Zvi; Hartman, Tamar Gur; Zelcer, Itay; Hugirat, Mohammad; Lev, Dorit; Lerman-Sagie, Tally; Blumkin, Lubov
Background: Congenital mirror movements are involuntary movements of a side of the body imitating intentional movements on the opposite side, appearing in early childhood and persisting beyond 7 years of age. Congenital mirror movements are usually idiopathic but have been reported in association with various brain malformations. Methods: We describe clinical, genetic, and radiologic features in 9 individuals from 5 families manifesting congenital mirror movements. Results: The brain malformations associated with congenital mirror movements were: dysplastic corpus callosum in father and daughter with a heterozygous p.Met1* mutation in DCC ; hypoplastic corpus callosum, dysgyria, and malformed vermis in a mother and son with a heterozygous p.Thr312Met mutation in TUBB3 ; dysplastic corpus callosum, dysgyria, abnormal vermis, and asymmetric ventricles in a father and 2 daughters with a heterozygous p.Arg121Trp mutation in TUBB; hypoplastic corpus callosum, dysgyria, malformed basal ganglia and abnormal vermis in a patient with a heterozygous p.Glu155Asp mutation in TUBA1A ; hydrocephalus, hypoplastic corpus callosum, polymicrogyria, and cerebellar cysts in a patient with a homozygous p.Pro312Leu mutation in POMGNT1 . Conclusion: DCC, TUBB3, TUBB, TUBA1A, POMGNT1 cause abnormal axonal guidance via different mechanisms and result in congenital mirror movements associated with brain malformations.